Identifikasi Pengetahuan dan Peran Perawat dalam Pelaksanaan Terapi Aktivitas Kelompok (TAK) d - Hesty, Hesty; Maimaznah, Maimaznah; Hidayat, Muhammad (Universitas Baiturrahim, 2024)
Therapeutic management of schizophrenia requires the role of nurses where the roles and functions of nurses include providing nursing care, as a family advocate, disease prevention, education, counseling, collaboration, ethical decision maker and researcher. One of the roles of nurses in schizophrenia patients is providing nursing care, namely Group Activity Therapy (TAK). Factors that can influence the implementation of an activity or action are knowledge, human resources, nursing management, tools, facilities, systems and technology. The aim of this research is to identify the knowledge and role of nurses in implementing Group Activity Therapy (TAK). Observation method on research subjects to determine the description of the knowledge and role of nurses in implementing group activity therapy. The population of this study was 150 people with a sample size of 61 people. Proportional random sampling technique for collecting samples. Data was obtained by filling out a questionnaire and analyzed univariately. The research results showed that 16 (26.2%) nurses had good knowledge, 26 nurses (42.6%) had sufficient knowledge and 19 (31.1%) had poor knowledge, 43 nurses (70.5%) had good and 18 (29.5%) had a poor role. It is hoped that the hospital will provide TAK training to nurses to increase knowledge and it is hoped that nurses can play a more important role in implementing TAK and provide better service to patients.